BABI : TERNAK KESAYANGAN ORANG MENTAWAI - Syaiful - Kasman (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2015)
Pig has always been an important dishes are always available in religious ceremony in Mentawai Ethnic. Starting from marriage, death, an inauguration of the new house (uma), birth of a child ceremony. Virtually every traditional ceremony (Punen) there is always a pig as consumption of religious ceremony